Mitchell, Barbara. Photograph of Joe Druken, Mary Ann Druken, Cecilia Doherty, and William Druken from Barbara Mitchell's personal photograph collection. - Jarvis, Dale
Left to right: Joe Druken, Mary Ann Druken, Cecilia Doherty, William Druken standing outside building.